167 Implementing a Community Researcher IRB Certification Through a Community-Engaged Approach. (April 2022) - Ott, Mary; Lynch, Dustin; Claxton, Gina
Abstract : OBJECTIVES/GOALS: A collaboration among Indiana CTSI community health partnerships (CHeP), bioethics, and regulatory programs identified and reviewed human research protection training programs targeting community engaged research, and pilot tested CIRTification with community partners working across a range of contexts. METHODS/STUDY POPULATION: We searched community human research protection training programs from across the county, identified three, examined each based upon criteria identified by community partners (time, relevance, online delivery) and our Human Research Protection Program (HRPP), and selected CIRTification (CIRT) to pilot. Ten community research partners volunteered to complete CIRT and a debriefing interview. Four completed CITI training previously. Participants included local and state-wide organizations, a resident, a state agency, and a hospital, and came from rural and urban communities. Interviews covered practical issues (ease of use, language, time), relevance, and comparison to CITI. Results were shared with HRPP for approval. RESULTS/ANTICIPATED RESULTS: Most felt CIRT was easy to navigate and engaging, and those who had done CITI felt CIRT was more relevant and engaging. The sections on historical background and recruitment were cited as most valuable. Suggestions were made to increase the diversity of examples beyond health care research. Community members mentioned several applications for CIRT including: (1) helping their own community work; (2) empowering them to be an advocate; (3) referring others to CIRT; (4) influencing approaches to recruitment and community engagement; and (5) applying ethics principles to their other community work. The Human Research Protection Program approved CIRT in place of CITI for community researchers. DISCUSSION/SIGNIFICANCE: Our process represents collaboration across the Indiana CTSI, HRPP and community partners, and use of best practices. Exemplifying "nothing about us without us", actions were based on direct input from community partners, with the goal of decreasing barriers to engaging communities in research.